Development of loaf bread from cassava starch-wheat flour composite - De la Cuesta, Jocelyn C. (1978)
This study was undertaken to determine the baking performance of cassava starch substituted at 25% and 50% for wheat flour in breadmaking. Volumes of loaf breads made from cassava starch-wheat flour composite are less than that from the control wheat flour. The greater the level of cassava starch in the composite mixture, the lesser the volume. The contour of the bread from composite flour vary with the level of cassava starch but there was little difference in color and flavor of the breads between the control and experimental samples. However, the texture of the loaves from the cassava starch-wheat flour composite was significantly different from the all-purpose wheat flour. With regards to its general acceptability, the control bread and the 25:75 flour composite bread were equally liked very much while the 50:50 cassava starch-wheat flour composite was rated neither like nor dislike to like slightly. The second phase was concerned with the effect of sodium stearoyl-2 lactylate (SSL) on loaf breads. With the addition of 0.25% and 0.50% SSL to the 25:75 and the 50:50 flour composite, the volume , as well as the texture was considerably improved. No significant differences in color and in flavor were observed in the resulting products, but the 50:50 cassava starch-wheat flour composite with 0.50% SSL appeared to be the most liked because it has the finest and the most even grain. Although it is quite unsymmetrical, it is the softest of all the samples.